Tinjauan Yuridis Kedudukan dan Fungsi Perjanjian Kerja Bersama dalam Hubungan Industrial - Herdiansyah Hamzah (Jurnal Risalah Hukum, 2009)
Work relationship between entrepreneur and worker constitutes a priority in the industrial relationship. Company’s smooth operation will be only determined from the maintenance of favorable relationship between both parties. Work relationship must be based on the fundamental guides or principles of agreement in binding both parties. The position and function of work agreement between worker and entrepreneur plays an important role in this case, which in the employment system of Indonesia, the term of “Cooperation Working Agreement” seems famously recognized. Such work agreement underlines favorable work relationship built through an attachment regulating the rights and obligations of each party. Therefore, the understanding over the position, function and the role of cooperation covenant in the work relationship should be important to realize harmonic and equal industrial relationship.